Peningkatan Laju Disolusi Trimetoprim dengan Teknik Co-Grinding Menggunakan Polimer Polivinilpirolidon K-30 - AUZAL HALIM; SYUKRAN HAMDENI; ERIZAL ZAINI (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Improvement of the dissolution rate of trimethoprim (TMP) as a model for a poorly water-soluble drug by solid state co-grinding technique with hydrophilic polymer polyvinylpyrrolidone K-30 (PVP K-30) using ball milling apparatus have been investigated. The ratios of drug to hydrophilic polymer were 1:1, 1:3 and 1:5. The solid state interaction of co-ground and physical mixture were characterized by powder X-ray diffraction, thermal DTA, SEM and FT-IR spectroscopy analysis. The dissolution studies were carried out in USP type I apparatus. The result of powder X-ray diffraction analysis showed that the co-grinding of TMP with PVP K-30 decreased the drug’s crystalinity. The endothermic peak of TMP of co-ground products shifted to lower temperature and peak intensity decreased significantly. Powder X-ray diffraction and DTA analysis indicated transformation of crystalline state of TMP to amorphous form by co-grinding with PVP K-30. FT-IR Spectra indicated that no chemical interaction between TMP and PVP K-30 in the co-grounds. Significant enhancement in dissolution rates were observed with the co-ground products of TMP and PVP K-30 as compared to the intact TMP and its physical mixture. In general, the dissolution rates of TMP in the co-grounds were enhanced as the polymer ratio increased.